The Use of Game-Based Learning in Teaching English Vocabulary for Junior High School Students': Teachers' Perceptions - Listyowati, Rini; Hidayat, Mohamad (Lingual Journal of Language and Culture, 2022)
This article aims to determine the teacher's perception of the implementation of based learning game in teaching vocabulary to junior high school students. The study method that was used in this research is descriptive qualitative. One teacher from each of the three types of SMP in Madura; Mts. Nahdlatut Thullab Omben, SMPI An-Nidhomiyah Pamekasan, and Mts. An-Nur Dharma Camplong participated in a semi-structured interview. data collection was done through interviews, observation and documentation. Five questions are submitted in Indonesian to make it easier for participants to comprehend and respond them and then transcribe to collect data. It the findings of this study are positive perceptions with teachers of the use of game-based learning as a medium for teaching vocabulary. They too agree that based learning game  is feasible to increase students' vocabulary because there are more advantages regardless of the challenges they face.